Kajian Etnobotani Mayarakat Adat Kampung Pulo di Kabupaten Garut - Nurlina Ramdianti; Hexa Apriliana Hidayah; Yayu Widiawati (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2013)
Ethnobotany is important in Indonesia because there are a lot of unknown things about the traditional plant usages by traditional people. One of them is the Kampung Pulo’s traditional people in Garut District of West Java’s province. This research aims to determine the diversity, usage and part of plants used by Kampung Pulo’s traditional people. The methods used are survey and data collection has been exploration, by interview and direct observation. The data were by analyzed by using descriptive analysis  plant diversity, usage for, part used and how they were used by Kampung Pulo’s traditional people. The result of the research showed that there were 93 plants species included into 42 families which is used to Kampung Pulo’s traditional people. The most species used includes Areca catechu L., Arenga pinnata (Wurmb) Merr., Cocos nucifera L., Carica papaya L., Sauropus androgynus (L.) Merr., Gigantochloa verticillata (Willd) Munro, Oryza sativa L., Curcuma domestica L., Kaempferia galanga L. and Zingiber Officinale Roscc.. Kampung Pulo’s traditional people use the plants in a wide variety way such as for foods, shelter, tools, drugs, cosmetics, rituals, dye and traditional ceremonies. Plant parts that often use continously are fruits, leaves, stems, flowers, tubers, saffrons and roots.